Academic Advisor System / Lim Tong Leong - Lim , Tong Leong (2002)
Today, information technology has pervaded into almost every industry in the country. Institution and universities today are moving toward paperless environment and computerized their current system to ensure smoother operations in the daily running operation. Academic Advisor System is introduced as to give new impluse for our university to gain competitive advantage. Academic Advisor System (AAS) is designed to enable academic advosir manage their student more effective. By using this system, academic advisor can view the result of the student and interact with them using chatting service that provided by the system. Beside that, the academic advisor also allows to make announcement at the web. So the student can read the announcement easily institution. The second purpose of AAS is let the student interact with the academic advisor and provide an alternative way to know their result beside the result slip. This report introduces the project and provides a description on the studied and researched during the literature review. It also describes the software development process that occurred in the project with detail on the system analysis and design. AAS will be integrates with the existing this because some of the information that is needed already existing in the current system. The system will use the same data resources and this is only saving the resource but also avoids duplication data in the different database. The duplication of data can cause many problems to the system and make the system fail. data in the different database. The duplication of data can cause many problems to the system and make the system fail.